2020
DOI: 10.18632/aging.103576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enriched branched-chain amino acid supplementation on sarcopenia

Abstract: To evaluate the effects of short-term administration of enriched branched-chain amino acids (BCAAs) on subjects with pre-sarcopenia or sarcopenia, our quasi-experimental study enrolled 33 subjects (12 pre-sarcopenia/21 sarcopenia; 6 men/27 women; mean age 66.6 ± 10.3 years) to take one sachet (3.6 g) of enriched BCAA powder twice a day for five weeks followed by a discontinuation period of 12 weeks. We evaluated sarcopenic parameters, including grip strength, 6-meter gait speed, and bioelectrical-impedance-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
0
30
0
1
Order By: Relevance
“…BCAA has a better efficacious energy substrate utilization in contrast to that of glucose and fatty acids. BCAA breakdown primarily takes place in the peripheral tissues (muscles, brain, and adipose tissue), extra-hepatically, so even if the hepatocytes are damaged and incapable of synthesizing protein in the liver, BCAA (especially leucine) in the muscles would promote protein synthesis, as concluded from the previous studies (1,23,26). Foremost, cirrhosis-related event, the hepatic encephalopathy, occurred less frequently in the BCAA group than in the ALB group.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…BCAA has a better efficacious energy substrate utilization in contrast to that of glucose and fatty acids. BCAA breakdown primarily takes place in the peripheral tissues (muscles, brain, and adipose tissue), extra-hepatically, so even if the hepatocytes are damaged and incapable of synthesizing protein in the liver, BCAA (especially leucine) in the muscles would promote protein synthesis, as concluded from the previous studies (1,23,26). Foremost, cirrhosis-related event, the hepatic encephalopathy, occurred less frequently in the BCAA group than in the ALB group.…”
Section: Discussionmentioning
confidence: 79%
“…The previous study on enriched BCAA supplementation on sarcopenic patients reports 25% improvement in the grip strength (23). According to those estimates, with G-power software, we calculated a sample size of 54 in each group with 80.0% statistical power to observe the effect size 0.5, and twosided effect in pre-and post-intervention matched pairs with β error of 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Leucine is important since it activates the mammalian target of rapamycin complex 1 (mTORC1) and the downstream phosphorylation of p70S6 kinase and 4E (eIF4E)-binding protein 1 (4E-BP1) and related signaling pathways [77]. The aging muscle is less responsive to lower doses of amino acids when compared to the young muscle and may require higher quantities of protein to acutely stimulate equivalent muscle protein synthesis [78]. Nevertheless, the dose and duration of BCAAs proposed here did not affect the cognition scores in our participants.…”
Section: Discussionmentioning
confidence: 99%
“…BCAA, with its anticatabolic effects, may provide a therapeutic target as shown in a study by Shirabe et al, where bacteremia rates were reduced in liver transplant recipients receiving oral BCAA supplements [ 52 ]. Studies have also shown beneficial effects of BCAA supplementation in several sarcopenic cohorts, including the elderly and patients with chronic liver disease comprising those with cirrhosis [ 53 , 54 , 55 , 56 , 57 , 58 ]. Furthermore, BCAA enhances muscle strength and mass [ 54 , 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%